Using SSM for structuring decision support in urban energy planning - Coelho, Dulce; Antunes, Carlos Henggeler; Martins, António Gomes (Technological and Economic Development of Economy, 2010)
This paper describes the use of Soft Systems Methodology (SSM) as a tool for problem structuring, which is the first phase encompassed in a methodological approach currently under development to provide decision support based on Multi‐Criteria Decision Analysis (MCDA) in energy planning problems in an urban context. In order to apply the methodology to a real‐world problem, a medium sized Portuguese city has been chosen as the decision setting. SSM is used for characterizing as precisely as possible the decision problem context, identifying the main stakeholders and their relations, and discerning the relevant criteria at stake for each one. Future work directions based on this phase are also envisaged.Article in English.Operacinės sistemos metodologijos taikymas planuojant miesto energetikąSantrauka. Straipsnyje aprašoma operacinės sistemos metodologija (OSM), kuri bus taikoma kaip daugiakriterinės analizės metodais pagrįsta sprendimų paramos sistema miesto energetikos planavimo problemoms spręsti. Siekiant metodologiją pritaikyti realiame gyvenime, eksperimentui buvo parinktas vidutinio dydžio Portugalijos miestas. Operacines sistemos metodologija taikyta kuo tiksliau nustatant pagrindines problemas, identifikuojant pagrindines suinteresuotas šalis ir jų santykius, nustatant vienas kitam įtaka darančius rodiklius. Numatytos būsimos darbo kryptys.Reikšminiai žodžiai: operacinė sistemos metodologija, daugiakriterinė sprendimų analizė, miesto energetikos planavimas.First published online: 10 Feb 2011